Canvas Business Model and Quality of Services in Clients of the Lodging Sector of the Junin Region - Paredes-Pérez, Marco A. J. (2022)
The use of a “business model to provide quality services in lodging establishments is essential for the development of this sector; Little research currently deals with this topic. The main objective of the study was to determine the association of the canvas business model and the quality of services in clients of lodging companies in the Junín region, the research was of a basic type, relational level with a descriptive-correlational design; the sample was made up of clients of lodging service in the Junín region, the sample was made up of 80 clients, the sampling technique was non-probabilistic for convenience (Otzen & Manterola, 2017), the approach was quantitative, the type of research Due to its purpose, it was basic, the level was descriptive and the design was not experimental-transversal; the theoretical methods were inductive-deductive and the empirical method was observational; the statistical test used was Kendall's tau b association coefficient, the scales were ordinal, the instruments were questionnaires prepared according to the literature review based on Osterwalder and Pigneur (2011) and Matsumoto-Nishizawa, (2014); the statistical treatment was carried out in SPSS 25; the main result was that there is a significant association between the canvas business model and quality of services in clients of the lodging sector of the Junín region, since the p-value found was 0,634 and the Kendall tau b statistic was 0.001, reflecting a significant relationship.